Asuhan Keperawatan dengan Penerapan Aroma Terapi Eucalyptus pada Pasien Anak (ISPA) dengan Masalah Gangguan Pernafasan di Desa Panggung Rejo Wilayah Puskesmas Sukoharjo Tahun 2024 - Maria Ulfa; Rice Hernanda; Sutrisno Sutrisno (Jurnal Ventilator, 2024)
Acute respiratory infection, or ARI, is an acute inflammation that most often occurs in children. It is caused by infection with microorganisms, bacteria or viruses or without or accompanied by inflammation of the lung parenchyma (David, 2019). Data from the World Health Organization (WHO) in 2019 shows that lower respiratory tract infections reduce life expectancy by 2.09 years in sufferers (WHO, 2019). The group most at risk is toddlers. This research uses a case study approach. Participant 1 was a three-year-old child patient who underwent ARI, data collection using interviews, observation, and physical examination. The tools and instruments used in this research were eucalyptus aromatherapy (eucalyptus oil), warm water and a family nursing care assessment format. After the data was collected, data analysis was carried out using the nursing process. The intervention emphasized airway clearance, but it was not adequate, so Eucalyptus aromatherapy was given for three days. The final evaluation was reached on the 3rd day, and the problem was resolved. The evaluation results showed that giving Eucalyptus aromatherapy to a three-year-old child who had respiratory problems was very effective so that on the third day, the child no longer experienced shortness of breath, the secretions were no longer there, and breathing became more accessible. Conclusions and suggestions for research sites should be made on how to apply eucalyptus aromatherapy to ARI to help expel secretions and relieve breathing.